Legal Evaluation of Womb Leases and Their Effects on a Born Child's Status - Siregar, Dahris; Derianus Hia, Petrus; Hulu, Tolomano; Jaya Hia, Delipinter Pasrah; Putra Laia, Martinus Aly (Universitas Islam Lamongan, 2024)
Abstract With the advancement of the times, things can develop quickly, such as the field of medicine in terms of uterine rental techniques, also known as surrogate mother. A uterus lease agreement is when the surrogate mother and a married couple agree to perform IVF (in vitro) technique, in which their sperm and ova are inserted into a tube, inserted into another woman's uterus. In order to do this, the author employs a normative legal research technique. The secondary data included in this study includes primary and secondary legal sources discovered through literature searches. The results showed that the womb lease agreement made is considered legally void, as well as affects the status of the child, which can occur in two cases: The kid born is an out-of-wedlock child if the surrogate mother is a female or widow. However, in situations where the surrogate mother is a lady who is still legally wed, so, the kid that the pair had who rents out her womb is considered their legitimate child.